2022
DOI: 10.1038/s41598-022-20270-z
|View full text |Cite|
|
Sign up to set email alerts
|

Stress responses to repeated captures in a wild ungulate

Abstract: While capture-mark-recapture studies provide essential individual-level data in ecology, repeated captures and handling may impact animal welfare and cause scientific bias. Evaluating the consequences of invasive methodologies should be an integral part of any study involving capture of live animals. We investigated short- and long-term stress responses to repeated captures within a winter on the physiology, behaviour, and reproductive success of female Svalbard reindeer (Rangifer tarandus platyrhynchus). Shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Examples of long-term effects of stressful situations include changes in body condition, calf survival rates, immune suppression, and habitat changes on an individual level, which could impact population dynamics due to reduced survival and reproductive rates (McLaren et al 2007;Moberg 2000). The literature on the long-term effects of immobilisation in free-ranging ungulates is limited with inconsistent conclusions (Larsen and Gauthier 1989;Omsjoe et al 2009;Trondrud et al 2022). A follow-up to the present study to evaluate long-term effects could be to look at the post-natal survivorship and slaughter weights of calves born in the spring after the immobilisation, as well as the reproductive rates of the females in the following years and their slaughter weights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of long-term effects of stressful situations include changes in body condition, calf survival rates, immune suppression, and habitat changes on an individual level, which could impact population dynamics due to reduced survival and reproductive rates (McLaren et al 2007;Moberg 2000). The literature on the long-term effects of immobilisation in free-ranging ungulates is limited with inconsistent conclusions (Larsen and Gauthier 1989;Omsjoe et al 2009;Trondrud et al 2022). A follow-up to the present study to evaluate long-term effects could be to look at the post-natal survivorship and slaughter weights of calves born in the spring after the immobilisation, as well as the reproductive rates of the females in the following years and their slaughter weights.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical immobilisation of free-ranging wildlife will always include the risk of adverse effects and mortality even in healthy animals, and mortality rates have traditionally been used to describe the negative impacts of wildlife capture (Hampton and Arnemo 2022;Kreeger and Arnemo 2018). In recent years, however, more studies have focused on the non-lethal adverse effects, including short-term physiological and behavioural effects on the individual animal and long-term impacts on both the individual and the population (Cattet et al 2008;Hampton and Arnemo 2022;Trondrud et al 2022). All stages of the immobilisation procedure could influence the animal both physiologically and behaviourally, and it is often not possible to distinguish which part of the capture process it comes from.…”
Section: Introductionmentioning
confidence: 99%
“…For health examinations to remain both ethical and beneficial it is also important to consider how the method of capture and restraint of sampled individuals can affect their overall welfare. To this end, among the many parameters measured by point-of-care analyzers, lactate is gaining much attention as it is often used as a proxy to evaluate stress level, generally considered an indicator of animal welfare, of sampled individuals ( Trondrund et al, 2022 ). A number of studies have shown how lactate levels in the blood can be used as a diagnostic tool for chronic conditions, but also as an indicator of stress associated with struggling, fear, and/or bursts of intense muscular activity in a number of species ( Rand et al, 2002 ; Klein et al, 2020 ; Trondrund et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies in reptiles and birds showed an increase in flight initiation distance to humans associated with capture and handling, likely due to aversive conditioning (Smith, 1996;Griffin and Boyle, 2009;Kidd-Weaver et al, 2022). In mammals, knowledge is more scant (Zaman et al, 2019;Trondrud et al, 2022), and also somewhat controversial: on the one hand, Zaman et al (2019) found no effect of captures on susceptibility to humans in golden marmotsMarmota caudata aurea . On the other hand, Trondrud et al (2022) showed a positive relationship between repeated captures within the same year and response behaviours towards humans in Svalbard reindeerRangifer tarandus platyrhynchus .…”
Section: Introductionmentioning
confidence: 99%